Effect of L-arginine on improvement of alveoli capillary wall thickness - Sri Sulistyowati; Yasir Avisena; Supriyadi Hari R (Universitas Airlangga, 2017)
Objectives: This study aims to demonstrate the effect of L-Arginine on pulmonary edema on mice preeclampsia model.Materials and Methods: This experimental analytic study was conducted on 30 pregnant mice divided into 3 groups, namely 10 normal pregnant mice (K1), 10 pregnant mice preeclampsia model (K2), and 10 pregnant mice pre-eclampsia model who received L-Arginine (K3) therapy. All subjects examined the thickness of the alveoli capillary wall in their pulmo using the Immunohisto-chemical method. The results were analyzed using Kruskal Wallis and Mann Whiteney tests.Results: Average alveoli capillary wall thickness (K1) 5.01±1.76/µm, (K2) 11.57±7.11/µm, with p value=0.00. Average alveoli capillary wall thickness (K3) 7.90±4.10/µm with p value=0.01.Conclusion: L-arginine affects to improve pulmonary edema in preeclampsia by reducing alveoli capillary wall thickness of the pulmonary in mice model.